ÁPIWAYÍ HÁM QURAMALÍ MODULLER BOYÍNShA JOQARÍ DÁREJELI SALÍSTÍRÍWLARDÍ ShEShIW USÍLLARÍ - Kalekeeva, T.T.; Maxsutova, U.D.; Quanıshbaeva, H.S. (SCIENCE and SOCIETY, 2025)
This article explores the problems of solving higher-order comparisons, where the methods of solving higher-order comparisons for simple and complex modules are solved using a few examples.